Efektivitas Penggunaan Model Pembelajaran Cooperative Learning dalam Mata Pelajaran Biologi Terhadap Hasil Belajar Siswa - Huda, Muhammad Komarul (Medan Resource Center, 2023)
This research evaluates the effectiveness of the Cooperative Learning instructional model in enhancing high school students' Biology learning outcomes. Employing an experimental design with pretest-posttest control groups, the study randomly selects two groups of students. Data collection methods include pretests, posttests, classroom observations, and questionnaires to assess interactions and perceptions. Descriptive and inferential statistics analyze significant differences in learning outcomes before and after implementing Cooperative Learning. Findings aim to inform educators, teachers, and stakeholders about the model's efficacy in Biology education. Implications suggest potential improvements in teaching strategies for Biology and other subjects, offering valuable insights for educational practitioners. This research contributes to understanding the Cooperative Learning model's effectiveness in enhancing students' learning outcomes, providing a basis for recommending more effective teaching strategies in various educational contexts.